Periodicity of molecular clusters based on symmetry-adapted orbital model - Takamasa Tsukamoto (Nature Portfolio, 2019)
Prediction of stable clusters based on the jellium model is limited because of the usual assumption of their spherical symmetry. Here the authors propose a symmetry adapted orbital model by quantum chemistry calculations for the prediction of stable clusters with various shapes that obey a certain periodicity.